Cashew gum (Anacardium occidentale L.) used as an alternative mounting medium in histological preparations (Research, Society and Development, 2022)
In this work, the objective was to use the resinous exudate of a typical plant of the Brazilian Northeast, the cashew tree gum (Anacardium occidentale L.) as an alternative mounting medium in the histological technique, economically viable and environmentally healthy. Cashew gum was processed according to the adapted method from Rinaudo and Milas. The refractive index reading, and the viscosity measurement were performed using an Abbes refractometer and an MVD-20 digital viscometer, respectively. According to the authorization of the Animal Use Committee of the Federal University of Pernambuco, different organs of Wistar rats were histologically processed and the permanent preparations were mounted with cashew resin gum (MGRC). The refractive index of the MGRC was 1.343 and the viscosity of the medium without mineral oil was 1143.7 ± 267.4 mPas.s and with the mineral oil it was 939.9 ± 103.7 mPas.s. The preparations mounted with MGRC, regardless of the type of stain used, presented with clear images and morphology of the structures conserved. The MGRC proved to be a satisfactory alternative to commercial assembly means, being economically viable and generating benefits such as personal biosecurity as it is non-toxic, in addition to not harming the environment.